(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2023)
This research is about determining the major rural development concept and programs implemented by the national government and how they impact the ordinary Filipino’s life satisfaction. the The study found that (1)The national rural development program is anchored on providing access to financing for agricultural production; (4) A significant part of the national rural development program is for calamity assistance (5) There is a slow pace of agrarian reform; (6) There is weak job creation in the rural areas thus period 2001-2009 has seen the most Filipinos forced abroad to find work in the country’s history wherein 1.42 million were deployed last year which was equivalent to almost 3,900 Filipinos leaving every day; and (7) There is the whole issue of livelihood sustenance, technical knowhow, technology, competition, cost of production, unpredictable calamities and most of all, ready markets for the produce in the rural areas. After twenty (20) years, the ordinary Filipno does not base his life satisfaction on whether or not the national government can develop the rural areas.